2021
DOI: 10.3389/fvets.2021.696841
|View full text |Cite
|
Sign up to set email alerts
|

Performance, Serum Biochemical and Immunological Parameters, and Digestive Enzyme and Intestinal Barrier-Related Gene Expression of Broiler Chickens Fed Fermented Fava Bean By-Products as a Substitute for Conventional Feed

Abstract: Improving the nutritional quality of unconventional feed ingredients such as fava bean by-products can enhance their utilization by broiler chickens. Hence, the quality of fermented fava bean by-products (FFB), in addition to growth, nutrient digestibility, digestive enzyme, and intestinal barrier-related gene expression, and serum biochemical and immunological parameters were evaluated in response to different levels of FFB. A total of 500 1-day-old broiler chicks (46.00 ± 0.388 g) were allocated to five grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 80 publications
(89 reference statements)
1
8
0
Order By: Relevance
“…At the beginning of rearing period, initial body weight was recorded and then the body weight and feed intake of rabbits in each group were estimated weekly for calculating the growth performance traits of rabbits at the rearing period (60 days of age) including the feed intake (FI), body weight gain (BWG) and feed conversion ratio (FCR) as previously detailed [ 34 , 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the beginning of rearing period, initial body weight was recorded and then the body weight and feed intake of rabbits in each group were estimated weekly for calculating the growth performance traits of rabbits at the rearing period (60 days of age) including the feed intake (FI), body weight gain (BWG) and feed conversion ratio (FCR) as previously detailed [ 34 , 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The small intestine of poultry is the major digestion and absorption site of nutrients, such as carbohydrates, proteins, and fats [ 38 ]. The digestive enzyme activity in intestinal digesta and mucosa is the main limiting factor affecting the FI, digestion, absorption, and growth of poultry [ 39 , 40 ]. Currently, there are various reports on the effects of probiotics on intestinal digestive enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…For optimum animal performance, the faba bean residues might require some nutrient supplementations or pre-treatments [54,55]. Omar et al [77] showed that microbial fermentation of faba bean by-products could enhance their nutritional value by increasing the concentration of crude protein and fat and decreasing the amount of crude fibre, lignin, and anti-nutrients. Similarly, the incubation of broad bean stalks with white-rot fungus Pleurotus ostreatus significantly improved their nutritive value [78].…”
Section: Harvest Residues-feed Usementioning
confidence: 99%